ОСОБЕННОСТИ РАБОТЫ РУЧНОГО ИНСТРУМЕНТА С ВЫСОКООБОРОТНЫМ ЭЛЕКТРОПРИВОДОМ - Антонов, А.Е. (Інститут електродинаміки НАН України, Київ, 2015)
The features of hand tools with a high-speed electric drive are considered. The mathematical model of the state of such device with non-rigid connection between the instrument casing and operator’s hands is created. Feature operation of the device consists in the occurrence of gyroscopic moment and nutation oscillations at a spatial turn casing, that may be unexpected for the operator. For research the elements of theory of the gyroscopic systems are used. Quantitative indicator, that characterize motion of casing with the gyroscopic reaction, is received. Information about the experimental research of damping time nutation oscillations of the device are given. References 4, figures 3.